Enforceability of the liquidated and ascertained damages and effect of section 75 contracts ACT 1950 - Mohamad, Shazlimanshah (2019)
The usual redress awarded to the employer in the event of a breach of contract due to late completion will be in the form of liquidated damages. Liquidated damages, or commonly known as Liquidated and Ascertained Damages, abbreviated as ‘LAD’ is sought as the sequel to a non-completion of work. The main issue in liquidated damages relating to Section 75 is relates to the claimable amount by the aggrieved party should contract violation happen. As deliberated in many law cases, the Courts have the discretion to award any other amount in the case of liquidated damages sum fixed in the contracts been challenged by the contractor as unreasonable. Hence this research is aimed to determine the requirements of damages entitlement for employer in the event of late completion by the contractor in accordance to the Contracts Act 1950 and also to determine whether the LAD clause in the contract is enforceable in relation to the court decision in Malaysia. Throughout this study, legal research will be conducted by using the case law as the research sources. The case laws are used for the purposes of data analysis. This study found that most of the court decisions, required the innocent party to prove his actual loss in claim for damages until the recent landmark decision by Federal Court in Cubic Electronics. The position of LAD in Malaysia has changed and shifted to the burden of proof pertaining the damages clause from the innocent party to the defaulting party. In the construction context, this means the contractor, and not the employer, will have to prove that the liquidated and ascertained damages clause and the sums stated therein are unreasonable.